Further clinical advancement of dendritic cell vaccination against ovarian cancer - Morehead, Lauren C.; Cannon, Martin J. (Annals of Research Hospitals, 2018)
Since the discovery of dendritic cells (DC) as potent stimulators of immune responses by Zanvil Cohn and Ralph Steinman in the 1970s, the idea that DC could be used as adjuvants for activation of antitumor immunity steadily gained traction, culminating in the first published clinical trial of DC vaccination (for treatment of B cell lymphoma) (1).